Optimization of Blanching Temperature and Nori Incorporation in the Production of Moringa oleifera-Based Food Seasoning - Mohammad Prasanto Bimantio; Aap Hidayah Maesa; Reza Widyasaputra (Journal of Applied Agricultural Science and Technology, 2026)
The utilisation of moringa leaves as a functional food ingredient is constrained by nutrient losses during thermal processing and limited sensory acceptability due to undesirable flavour characteristics. Optimising blanching conditions while incorporating umami-rich nori is therefore essential to improve antioxidant retention, nutritional quality, and consumer acceptance of moringa-based seasonings. This study aimed to optimise blanching temperature and nori incorporation in the formulation of moringa flake (Bon Kelor), a functional food seasoning. A factorial experimental design was employed with three blanching temperatures (70°C, 80°C, and 90°C) and three levels of nori (5%, 10%, and 15%). Analyses included antioxidant activity (DPPH), proximate composition, sodium content, and hedonic sensory evaluation. The results showed significant effects of both blanching and nori concentration on antioxidant activity, macronutrient levels, and organoleptic properties (p < 0.05). The best formulation was obtained at 90°C with 15% nori, featuring high antioxidant activity (73.72%), protein (18.34%), and energy (370.39 kcal/100 g). The by-difference method revealed increased carbohydrate content with nori addition, attributed to water-soluble polysaccharides. Sensory analysis confirmed high panellist acceptance for colour, aroma, and taste. Blanching enhanced nutrient retention, reduced moisture, and improved flavour. In summary, combining thermal treatment with seaweed enrichment offers a valuable strategy to produce nutritious and acceptable moringa-based food products.